Exploring Coconut Oil as a Green Substitute for Xylene in Histology Clearing: A Thorough Literature Review on Enhanced Quality Descriptions - Kharomah, Intan Fadhila; Nailufar, Yuyun (The Indonesian Institute of Science and Technology Research, 2024)
Coconut oil, derived from tropical plants, contains steroid compounds, tocopherols, and tocotrienols that can replace alcohol in tissue preparations. These substances are then substituted with solutions that bind effectively to paraffin. The primary objective of this study is to evaluate the quality of histology preparations using natural ingredients, specifically coconut oil and xylene, as alternatives in the clearing process. Utilizing the literature review method, we accessed research journals from Google Scholar and Pubmed databases, focusing on PICO keywords within 2013-2022. The findings indicate that coconut oil can efficiently clear tissue preparations, allowing paraffin to permeate the tissue's pores. This, in turn, enhances the visibility of cellular structures such as the nucleus and cytoplasm when observed under a microscope. The study highlights coconut oil as a credible substitute for xylene, recognizing its ability to produce high-quality histology preparations. Its adoption as an alternative to xylene is attributed to its eco-friendly composition and non-toxic properties, positioning it as a promising choice for advancing histological techniques.